(untitled) (Brazilian Journal of Health Research, 2020)
Introduction: Neoplasms affecting salivary glands are relatively rare, although they account for a wide variety of biological behaviors and histological subtypes of benign and malignant tumors. Objective: Determining the relative frequency and distribution of a series of 124 cases histopathologically diagnosed as primary salivary gland neoplasms. Methods: Exploratory cross-sectional study comprising salivary gland neoplasm cases diagnosed at Napoleon Laureano Hospital, João Pessoa City, from January 2002 to December 2012. Recorded data encompassed patients, sex, age, race, anatomical site, affected gland type, as well as tumor size, nature and histopathological diagnosis. Collected data were analyzed through descriptive statistics. Results: 124 cases were identified, 98 (79.03%) were benign and 26 (20.97%) were malignant tumors. With respect to anatomical site, most tumors were observed in the parotid gland (84.7%), and it was followed by minor salivary (8%) and submandibular glands (7.3%). Minor salivary gland tumors were more often diagnosed in the palate. Pleomorphic adenoma (87.8%) was the most common benign tumor, whereas adenoid cystic carcinoma (42.3%) was the most common malignant tumor. Malignant tumors were mostly observed in the parotid (76.9%) and minor salivary glands (23%). Conclusion: Statistical data presented in the current study may help better understanding the clinical and biological features of salivary gland tumors.